DAMPAK CTL (CONTEXTUAL TEACHING AND LEARNING) TERHADAP HASIL BELAJAR MEMBACA PEMAHAMAN PAI TARUNA TINGKAT I JURUSAN TEKNIK PENERBANGAN STPI CURUG - Alwazir Abdusshomad (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
The aims of this research were to reveal the impact of contextual teaching and learning of PAI based on the Cadets’ motivation and to find out the combined effect of the approach of learning and motivation of learning to Cadets’ achievement in reading comprehension of PAI. This research was a quasiexperiment with Cadets’ achievement of reading comprehension as the dependent variable and the approach of instruction and the Cadets’ learning motivation as the independent variable. This study used the factorial 2 x 2 experimental design with two qualification independent variables which were contextual teaching and learning, and convensional learning. The population of this research was all forth grade Cadets level 1 department of flight engineering STPI Curug with the sampel of 61 Cadetss. The instruments of the data collection were a test of Cadets’ achievement and a questionnaire of learning motivation. The technique of data analysis was two tails variance analysis followed by Sheffe test. The result of the study shows that (1) there are differences in achievement of the Cadets who were taught by using contextual teaching and learning from those who were taught using the convensional learning. The result of Anava calculation shows that there was significant differences in reading comprehension (Fhitung = 21.293 > Ftabel = 4.012,  = 0.05) between those who were taught by using the contextual teaching and learning, and those who were taught by using the convensional learning